Armored victory 1945 : U.S. Army tank combat in the European theater from the Battle of the Bulge to Germany's surrender /: U.S. Army tank combat in the European theater from the Battle of the Bulge to Germany's surrender. (2022) - Zaloga, Steve, 1952-
No abstract available